Community Empowerment through Utilization of Moringa Plants as a Business Startup - Purwanti, Ari; Amalia, Mekar Meilisa; Asrijal, Andi; Maq, Mumu Muzayyin; Faliza, Nur; Roefaida, Effy (Amalee: Indonesian Journal of Community Research and Engagement, 2023)
Moringa plants have the potential as raw materials for value-added products, such as processed foods, beverages, health supplements, cosmetics, and others. Citali Village has the potential to become a Moringa village. However, it has obstacles in the mindset of the community toward Moringa. They still think that Moringa is for mystical things. This service aims to change people's attitudes about Moringa and make people able to process Moringa into a product. This service method uses the ABCD (Asset-Based Community Development) approach. As a result of this dedication, the people of Citali village have understood the benefits and how to cultivate and process Moringa into a product; it is hoped that it can improve the welfare of the people of Citali village. The impact of this community service activity is that the people of Citali Village can understand and better understand what Moringa is in a more positive and modern way and can process Moringa into a valuable product.